Work Identity and Future Research on Work as a Calling. (October 2022) - Reed, Americus; Jones, Samuel; Dik, Bryan J.
Research on work as a calling is gaining momentum, and work-as-a-calling theory is providing a helpful deductive structure to the consistent evidence that people who view their work as a calling and can actively live out that calling usually experience both career-related and general well-being. What is less clear are the key processes that may lead people to perceive a calling in the first place. By bringing work identity into sharper focus, we propose an especially promising framework for constructing a sense of calling, one that uses a cognitive approach. This cognitive approach to eliciting a sense of calling builds on four key work-identity precursors: effort calculation, reflection, appraisal, and fusion. These forward-looking processes are supported by extant research and are promising areas for future research that can illuminate how people may come to perceive a calling.